Analisa Penyebab Rework Pada Proses Produksi Produk Furniture Polo Showcase 2df Wht Menggunakan Metode Failure Mode And Effect Analysis (Fmea) - Prastyo Utomo; Dira Ernawati (Jurnal Kendali Teknik dan Sains, 2024)
As innovation develops and the human population increases, product competition between companies increases, so producers are required to produce goods as quickly as possible while still considering the quality aspects of the product. PT. Cipta Oggi is a company engaged in furniture production. PT. Cipta Oggi has several types of production, namely office tables, cupboards, TV shelves and decorative cupboards. In the production process for the 2DF WHT polo showcase furniture product, it has the highest rework rate, namely 10.67%. The method used in this research is the FMEA method. The FMEA method will later produce output results in the form of an RPN from which recommendations for improvement will be obtained from the types of causes of failure that are the highest. With this research, the aim is to analyze the causes of rework in the production process of Polo Showcase 2DF WHT furniture products which can later reduce the rework rate.